Pengaruh pemanfaatan musik sebagai stimulus kognitif terhadap peningkatan penguasaan kosakata bahasa inggris pelajar : Tinjauan literatur - Rohman, Fatiha Nur (Maliki Interdisciplinary Journal, 2026)
Vocabulary acquisition is a primary challenge in English as a Foreign Language (EFL) learning. This study aims to examine the influence of utilizing music as a cognitive stimulus on improving students' vocabulary mastery through a systematic literature review. The method involves a synthetic analysis of seven relevant literature sources, including experimental and media development studies. The review findings indicate that music, in the form of both songs and instrumental tracks, functions as an effective mnemonic tool to enhance attention and lexical memory retention. Rhythm and melody provide a context for enjoyable repetition, thereby reducing students' affective filters. In conclusion, music is not merely an entertainment medium but a strategic cognitive stimulus that significantly accelerates vocabulary acquisition. The implications of this study encourage educators to integrate musical elements into curricula and technology-based learning media to optimize language learning outcomes.